PENGGUNAAN “APE MAGIC STRAWS” DALAM MENINGKATKAN MOTORIK HALUS ANAK USIA DINI - Muchamad Arif; Lianatus Shofiyah (MOTORIC, 2021)
This study aims to determine the success of the implementation of teaching aid design "APE Magic Straws" TK RA Qurrata A'yun. Whether the learning media succeed in achieving the formulated goals, namely to develop aspects of early childhood development. It used qualitative descriptive. It was conducted for 4x meetings, each meeting 30 minutes and in its application it can be adjusted to the existing theme. The research subject was 20 students. APE Magic Straws can help introduce geometric shapes, colors, calculations and designs to form anything. The results showed that the APE Magic Straws can stimulate all aspects of early childhood development and make children excited about learning, fun and not boring. However, for children whose physical motor skills are weak, they need a longer time to apply. Keywords: teaching aids, geometric shapes, magic straws, APE design